MRCK-Alpha and Its Effector Myosin II Regulatory Light Chain Bind ABCB4 and Regulate Its Membrane Expression - Alix Bruneau; Jean-Louis Delaunay; Anne-Marie Durand-Schneider; Virginie Vauthier; Amel Ben Saad; Lynda Aoudjehane; Haquima El Mourabit; Romain Morichon; Thomas Falguières; Jérémie Gautheron; Chantal Housset; Tounsia Aït-Slimane (Cells, 2022)
ABCB4, is an adenosine triphosphate-binding cassette (ABC) transporter localized at the canalicular membrane of hepatocytes, where it mediates phosphatidylcholine secretion into bile. Gene variations of ABCB4 cause different types of liver diseases, including progressive familial intrahepatic cholestasis type 3 (PFIC3). The molecular mechanisms underlying the trafficking of ABCB4 to and from the canalicular membrane are still unknown. We identified the serine/threonine kinase Myotonic dystrophy kinase-related Cdc42-binding kinase isoform α (MRCKα) as a novel partner of ABCB4. The role of MRCKα was explored, either by expression of dominant negative mutant or by gene silencing using the specific RNAi and CRISPR-cas9 strategy in cell models. The expression of a dominant-negative mutant of MRCKα and MRCKα inhibition by chelerythrine both caused a significant increase in ABCB4 steady-state expression in primary human hepatocytes and HEK-293 cells. RNA interference and CRISPR-Cas9 knockout of MRCKα also caused a significant increase in the amount of ABCB4 protein expression. We demonstrated that the effect of MRCKα was mediated by its downstream effector, the myosin II regulatory light chain (MRLC), which was shown to also bind ABCB4. Our findings provide evidence that MRCKα and MRLC bind to ABCB4 and regulate its cell surface expression.